Large Bowel Obstruction as Unusual Presentation of Pancreatic Tail Cancer - Abd Aziz, Mohd Fahmi; Sainal, Mohd. Yusof; Azmi, Norshisham; Elagili, Faisal; Amjad, Nasser Muhammad; Md Noor, Azmi (2020)
OBJECTIVE We aim to report a rare case of large bowel obstruction due to pancreatic adenocarcinoma. CASE REPORT A 58 years old chronic smoker male presented to the emergency room with progressive abdominal distention started 3 weeks prior. It was associated with absolute constipation but no nausea or vomiting. Clinically, the patient appeared cachectic, abdomen was grossly distended, tympanic and tender to palpation. Rectal examination was unremarkable. Computerized Tomography (CT) of abdomen demonstrated diffuse dilatation of large and small bowel with possible transition zone at the splenic flexure area. The patient underwent an emergency explorative laparotomy, At the operation, there was a mass involving the left colonic flexure, the spleen and pancreatic tail was found. Left hemicolectomy, from the hepatic flexure to the upper sigmoid colon, was performed, with the spleen and the distal half of the pancreas being excised. A double barrel stoma was performed. The histology showed ductal adenocarcinoma with primary location in the pancreatic tail, invading the colon and metastasis to the spleen. Postoperative period was uneventful except for hospital acquired pneumonia which was managed with antibiotic. He was discharged on day 21 after surgery. Unfortunately, a week after, he succumbed when he presented with recurrent pneumonia with severe sepsis. CONCLUSION Although rare for pancreatic adenocarcinoma to have the same presentation as colon cancer, and should therefore be considered in the differential diagnosis of large bowel obstruction.